Self-Regulatory Initiatives and Authority Recommendations for use on the Bancassurance Market - Pisarewicz, Piotr (Studia Oeconomica Posnaniensia, 2015)
The purpose of this paper is to analyze the effectiveness of selected issues of sectoral recommendations issued by the Polish Chamber of Insurance (PIU) and the Association of Polish Banks (ZBP) in the context of the draft Recommendation U , which is submitted to the Financial Authority Commission. The new document introduces the highest standards in bancassurance, which cancels the existing practices of financial institutions causing conflict of interest. Existing legislation for the sector proved to be insufficient in this regard. The areas of Recommendation U will cover both management, information, reporting, internal supervision and compliance, which go far beyond the current self-regulatory arrangements. The present sectoral regulations are inadequate in this respect which was one of the main reasons behind the proposal for a new recommendation.